2006
DOI: 10.1590/s0004-27302006000300005
|View full text |Cite
|
Sign up to set email alerts
|

Distribuição e freqüência de alelos e haplotipos HLA em brasileiros com diabetes melito tipo 1

Abstract: RESUMOA predisposição genética ao diabetes melito tipo 1 (DM1) é associada a múltiplos genes do sistema de histocompatibilidade humano (HLA) de classe II. Em caucasianos, os antígenos HLA-DR3 e -DR4 são associados à susceptibilidade e o -DR2, à proteção. No Brasil, um país constituído por grande miscigenação entre caucasianos europeus, índios nativos e negros africanos, a base genética do DM1 tem sido pouco estudada. O objetivo desse trabalho foi apresentar uma revisão crítica dos artigos indexados nos bancos … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0
6

Year Published

2007
2007
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 29 publications
1
3
0
6
Order By: Relevance
“…Even more disturbing is the fact that the prevalence of T1DM in Brazilian children under age 15 is estimated to be around 7.6 individuals affected per 100000 subjects in the State of Sao Paulo (95% confidence interval, 5.6-9.7) [31] and other parts of the country [32]. Recent eight genetic studies conducted in the Southern regions of Brazil [33], including one carried out by our group in the Sao Paulo area [34], demonstrated that the susceptibility to T1DM was associated with HLA-DR*03, -DR*04, -DQB1*0201, and -DQB1*0302 alleles, whereas HLA-DRB1*15, *11, and *13, DQB1*0602/*0603/*0301 alleles conferred a protective effect.…”
Section: Introductionmentioning
confidence: 99%
“…Even more disturbing is the fact that the prevalence of T1DM in Brazilian children under age 15 is estimated to be around 7.6 individuals affected per 100000 subjects in the State of Sao Paulo (95% confidence interval, 5.6-9.7) [31] and other parts of the country [32]. Recent eight genetic studies conducted in the Southern regions of Brazil [33], including one carried out by our group in the Sao Paulo area [34], demonstrated that the susceptibility to T1DM was associated with HLA-DR*03, -DR*04, -DQB1*0201, and -DQB1*0302 alleles, whereas HLA-DRB1*15, *11, and *13, DQB1*0602/*0603/*0301 alleles conferred a protective effect.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge few information concerning the distribution of HLA alleles and haplotypes associated with T1D in Brazilian population have been reported [18,19]. HLA typing is known to be time-consuming and expensive; thus, new genotyping methods for the discrimination of the most prevalent T1D risk haplotypes aimed at cost reduction and automation would be greatly beneficial.…”
Section: Introductionmentioning
confidence: 99%
“…O desencadeamento da reação inflamatória parece depender tanto de fatores genéticos quanto ambientais (8)(9)(10). Dentre os fatores ambientais envolvidos na gênese do DM1, destacam-se os vírus, proteínas do leite de vaca e toxinas (estreptozotocina, aloxana) (10).…”
Section: Diabetes Mellitus Tipounclassified
“…O lócus IDDM-1, localizado no cromossomo 6p21, é o mais importante, respondendo por aproximadamente 30-50% da agregação familiar da doença (9). Esse gene codifica moléculas HLA de classe II presentes na superfície das células apresentadoras de antígenos (células dendríticas, macrófagos e linfócitos B) que participam do processo imune apresentando antígenos aos linfócitos CD4 + (8,9 No lócus IDDM-12, localizado no cromossomo 2q33, encontra-se o gene CTLA-4 (cytotoxic T lymphocyte-associated antigen), que codifica receptores co-estimuladores nas células T levando à sua ativação (12).…”
Section: Diabetes Mellitus Tipounclassified
See 1 more Smart Citation